2020
DOI: 10.1111/tan.13817
|View full text |Cite
|
Sign up to set email alerts
|

Killer‐cell immunoglobulin‐like receptor assessment algorithms in haemopoietic progenitor cell transplantation: current perspectives and future opportunities

Abstract: Natural killer cells preferentially target and kill malignant and virally infected cells. Both these properties present compelling clinical utility in the field of haemopoietic progenitor cell transplantation (HPCT), potentially promoting a graft vs leukaemia effect in the absence of graft vs host disease and protecting against cytomegalovirus activation. Killer Ig-like receptors (KIR) play a central role in the cytotoxic action of natural killer cells, providing opportunity for improving transplantation outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
(172 reference statements)
0
4
0
3
Order By: Relevance
“…Counterintuitively, this clinical study ( 75 ) has shown that recipients not lacking the KIR–ligand of the cognate donor experienced better overall survival in leukemia patients, in contradiction with the receptor–ligand model ( 76 ). Nowak et al.…”
Section: Kir Alloreactivity Assessmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Counterintuitively, this clinical study ( 75 ) has shown that recipients not lacking the KIR–ligand of the cognate donor experienced better overall survival in leukemia patients, in contradiction with the receptor–ligand model ( 76 ). Nowak et al.…”
Section: Kir Alloreactivity Assessmentmentioning
confidence: 86%
“…also hypothesize that couples predicted as alloreactive by the receptor–ligand model could have lymphocytes remaining largely hyporesponsive to stimulus, as the receptor–ligand model does not take into account donor NK cell education ( 79 ). However, the proportion of favorable couples fitting the educational model is small, meaning that only few D/R couples could benefit ( 76 ).…”
Section: Kir Alloreactivity Assessmentmentioning
confidence: 99%
“…Without ground truth available, without any reason to expect this cohort to deviate from expectations, and considering KIR*IMP's self-reported accuracy, the evidence suggests that KPI's predictions are more accurate than KIR*IMP's in this cohort and specifically that KIR*IMP under called the presence of genes KIR2DS2, KIR2DL2, KIR2DS3, KIR2DL5 and haplotypes cB01~tA01 and cB02~tA01. As reviewed recently by Wright et al, this may be particularly relevant in the context of hematopoietic stem cell transplantation, where some case/control studies claim an important role for these regions (19). There are several potential reasons KIR*IMP's predictions may be less accurate than KPI's.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have led to the combination of KIR and HLA genotyping in the selection of stem cell donors. Discussion of the selection of unrelated HSCT donors based on HLA and KIR genotyping is outside of the scope of this article but is reviewed by Wright (2020).…”
Section: Kir Content and Transplantationmentioning
confidence: 99%